Microbial biodiversity in the throats of pulmonary tuberculosis patients and tuberculin skin test (TST) positive and negative healthy individuals in Malaysia. (September 2020) - Semail, Noreafifah; Suraiya, Siti; Calero, Romel; Mirabal, Mayelin; Carrillo, Humberto; Ezzeddin Kamil, Mohamed Hashim; Sarmiento, Maria E.; Acosta, Armando; Norazmi, Mohd Nor
Abstract: The purpose of this study was to investigate the composition of throat microbiota in pulmonary tuberculosis patients (PTB ) in comparison to healthy tuberculin skin test positive (TSTp ) and negative (TSTn ) individuals. Throat swabs samples were collected, and the microbiota was characterized. Richer operational taxonomic units (OTUs) were present in PTB group, compared to TSTp and TSTn. Regarding alpha diversity analysis there was a higher community diversity in TSTn compared to TSTp. Beta diversity analysis showed different species composition in TSTp compared to TSTn and PTB. There was higher presence of Firmicutes in PTB and TSTn compared to TSTp group at phylum level. At the genus level, Leuconostoc and Enterococcus were higher in TSTn compared to TSTp and Pediococcus, Chryseobacterium, Bifidobacterium, Butyrivibrio, and Bulleidia were higher in PTB compared to TSTn. Streptococcus was higher in TSTn compared to PTB and Lactobacillus in PTB compared to TSTp. At species level, Streptococcus sobrinus and Bulleidia moorei were higher in PTB compared to TSTn individuals, while Lactobacillus salivarius was higher in PTB compared to TSTp. The differences in the microbiome composition could influence the resistance/susceptibility to Mtb infection.